Lattice assisted dielectric relaxation in four-layer Aurivillius Bi5FeTi3O15 ceramic at low temperatures. (8th July 2021) - Prajapat, Deepak; Surampalli, Akash; Schiesaro, Irene; Kaushik, S D; Meneghini, Carlo; Sagdeo, Archna; Sathe, V G; Siruguri, V; Welter, Edmund; Reddy, V Raghavendra
Abstract: We have investigated magnetic, structural and dielectric properties of Bi5 FeTi3 O15 (BFTO) in the temperature range 5K–300 K. Using diffraction, Raman spectroscopy and x-ray absorption fine structure measurements, iso-structural modifications are observed at low temperatures (≈100 K). The analysis of dielectric constant data revealed signatures of dielectric relaxation, concomitant with these structural modifications in BFTO at the same temperatures. Further, employing complementary experimental methods, it is shown that the distribution of Fe/Ti ions in BFTO is random. With the help of techniques that probe magnetism at various length and time scales, it is shown that the phase-pure BFTO is non-magnetic down to the lowest temperatures.